2020
DOI: 10.3390/app10217540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Boundary Condition on Tilting Pad Journal Bearing Behavior

Abstract: This research presents the effect of the thermal boundary condition on the tilting pad journal bearing characteristics. The thermal boundary condition includes the temperature around the bearing pad, spinning journal, and lubricant supply temperature. Change in bearing performance according to the temperature around each element constituting the bearing was analyzed without paying attention to how the actual thermal boundary conditions around the bearing are configured. High fidelity numerical model of tilting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It can be seen that the performance difference between the smooth bearing and the bearing with composite texture is more obvious when thermal effects are considered. As Figures [13][14][15][16][17][18][19][20][21][22] show that, the carry capacity of composite textured bearing is increased by about 40%-50% compared to smooth bearing, and the friction coefficient of composite textured bearing can be reduced to about 25% of the smooth bearing. Take the optimal values in each figure to obtain the increase rate of carry capacity and the decrease rate of friction coefficient as shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the performance difference between the smooth bearing and the bearing with composite texture is more obvious when thermal effects are considered. As Figures [13][14][15][16][17][18][19][20][21][22] show that, the carry capacity of composite textured bearing is increased by about 40%-50% compared to smooth bearing, and the friction coefficient of composite textured bearing can be reduced to about 25% of the smooth bearing. Take the optimal values in each figure to obtain the increase rate of carry capacity and the decrease rate of friction coefficient as shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…It is concluded that ceramic bearing can improve working temperature of bearing. Suh et al 14 obtained the influence law of different thermal boundary conditions and lubricants on the performance of journal bearings. Zhao et al 15 solved the generalised Reynolds equation and calculated bearing deformation under action of oil film pressure and heat by the compliance matrix method.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of synchronous coefficients tends to overestimate stability, especially in the case of a high Sommerfeld number [13] so the sub-synchronous dynamic coefficients are quite important. Suh studied the effects of thermal boundary condition on the stiffness and damping coefficients for tilting pad bearings [14]. Experimental studies of tilting pad bearings also indicated the frequency dependence of dynamic coefficients [15].…”
Section: Introductionmentioning
confidence: 99%
“…Chatterton et al [39] predicted the performance of the tilting pad journal bearing when the pad cooled by various methods and compared it with the experimental results. Suh et al [40] predicted the change of static and dynamic characteristics under various temperature boundary conditions around the tilting pad journal bearing.…”
Section: Introductionmentioning
confidence: 99%